2002
DOI: 10.1097/00005537-200209000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Resistant Pseudomonas to Ciprofloxacin in Malignant Otitis Externa

Abstract: In our series, resistance to ciprofloxacin in patients with malignant otitis externa is increasing over time. This may have an impact on the relatively successful outpatient treatment of these patients in the past decade. A return to inpatient or outpatient intravenous treatment with third-generation cephalosporins/antipseudomonal penicillins and more frequent debridement will be required in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
82
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 13 publications
6
82
1
1
Order By: Relevance
“…However, oral Fluoroquinolones like Ciprofloxacin have far superior antipseudomonal action, replacing the need for intravenous antimicrobials, along with excellent penetration into bones, making them the drugs of choice for MOE [41][42][43]. Another advantage offered by Quinolones has been safe administration in elderly diabetics with an already deranged renal functionality.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, oral Fluoroquinolones like Ciprofloxacin have far superior antipseudomonal action, replacing the need for intravenous antimicrobials, along with excellent penetration into bones, making them the drugs of choice for MOE [41][42][43]. Another advantage offered by Quinolones has been safe administration in elderly diabetics with an already deranged renal functionality.…”
Section: Treatmentmentioning
confidence: 99%
“…Patients are usually discharged with an oral Ciprofloxacin along with appropriate antifungal if fungal smears are positive. The widespread use of oral fluoroquinolones along with incomplete treatment course for MOE, has led to increase in reports of resistance [43].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Bergholz and assoc. in their study proved that 33% of MOE caused by Pseudomonas bacretia showed high resistency on Ciprofloxacin [10]. Standard laboratory tests include sedimentation rate of erythrocytes, CRP, leukocyte formula, fibrinogen, hematocrit and glucose but all unspecified so these tests have to match the complete diagnostic picture in order for MOE to be adequately diagnosed and treated [9].…”
Section: Discusionmentioning
confidence: 99%
“…Increasing numbers of ciprofloxacin-resistant Pseudomonas infections means that identifying antibiotic sensitivity remains important. 17 Mortality data in NOE is poorly documented, but fatal events are usually due to intracranial complications such as dural sinus thrombosis, meningitis and intracranial abscesses. 5,9 A recent case series of 46 patients treated for NOE quoted healing rates over 95% after a mean follow-up of around 78 weeks.…”
mentioning
confidence: 99%